(untitled) (Global Journal of Science Frontier Research, 2012)
In this paper we extend Prof. Yang Chunyan and Prof. Cai Wen’s dependent function of a point P with respect to two nested sets X 0 ⊂ X, for the case the sets X 0 and X have common ending points, from 1Dspace to n-D-space. We give several examples in 2Dand 3D-spaces. When computing the dependent function value k(.) of the optimal point O, we take its maximum possible value. Formulas for computing k(O), and the geometrical determination the Critical Zone are also given.